PERINATAL OUTCOME OF FETAL GROWTH RESTRICTION AND FACTORS ASSOCIATED WITH IT AT ASELLA TEACHING AND REFERRAL HOSPITAL, SOUTH-EAST ETHIOPA - Gezahegn, Melese; FIKADU, ANDUALEM; TAFA, MESFIN (Ethiopian Journal of Reproductive Health, 2025)
Background: Fetal growth restriction (FGR) is a disorder of fetal growth and development due to decreased nutrients and oxygen supply to the fetus. It is caused by placental insufficiency during intrauterine life. FGR is associated with a variety of adverse perinatal outcomes. There is scarcity of data on perinatal outcomes of FGR and factors associated with it in the study area. Methods: Hospital based cross sectional study was conducted in Asella teaching and referral Hospital from February 1, 2022 to September 30, 2022. A total of 172 study participant were enrolled. Data was entered into epidata version 4.6 and exported to SPSS version 26 for data cleaning & analysis. Logistic regression was done to look for factors associated with unfavorable perinatal outcome. The result was presented using 95% confidence interval of crude and adjusted odds ratios. P-value < 0.05 was used to declare statistical significance. Result: There were a total of 172 FGR deliveries during the study period. Of these deliveries 107(62.2%) cases have unfavorable perinatal outcome. The odds of having unfavorable perinatal outcome were decreased by 90.2% among mothers 20-34 years (AOR; 0.098, 95% CI: 0.016-0.58). Mother with pre pregnancy BMI between 18.5 -24.9kg/m2 has associated with decreased odds of developing unfavorable perinatal outcome by 80% (AOR; 0.20., 95% CI: 0.07-0.55). Stage 1 FGR and stage 2 FGR were associated with 9.1 times and 22.6 times increased odds of developing unfavorable perinatal outcome when compared with stage 0 FGR (AOR; 9.07, 95% CI: 2.83-29.10) and (AOR; 22.66, 95%CI: 1.84-278.55) respectively. Mother who has no known risk factor for FGR has decreased odds of developing unfavorable perinatal outcome by 79% (AOR; 0.21, 95%CI: 0.049-0.91) while mother who has any form of hypertension has 5.8 times increased odds of developing unfavorable perinatal outcome (AOR; 5.83, 95% CI: 1.14-29.7). Conclusions and Recommendation: Maternal age, pre pregnancy BMI, stage of FGR, known maternal risk factor for FGR, and presence of maternal hypertension were significantly associated with unfavorable perinatal outcome. We recommended counseling women on nutrition so as to increase their pre-pregnacy BMI before getting pregnant and to intervene for minimizing risk of FGR development in the community.